Dynamic Observation of the Effect of Maternal Caries on the Oral Microbiota of Infants Aged 12–24 Months - Li, Fei; Fu, Ding; Tao, Danying; Feng, Xiping; Wong, May Chun Mei; Xu, Wei; Lu, Haixia (Frontiers in Cellular and Infection Microbiology, 2021)
Aim: To provide a dynamic description of the oral microbial composition in mothers with and without dental caries and their children aging 12-24 months. Methodology: A total of 20 pairs of mothers and their children aged 12 months were included and followed up at 18 and 24 months of age. Ten mothers with dental caries (MEG) and their children (CEG) were in the exposure group, and ten caries-free mothers (MCG) and their children (CCG) in control group. Supragingival plaque biofilm samples were collected and DNA was extracted for bacterial 16S rRNA gene sequencing. Results: A total of 18 pairs completed follow-ups. At a 3% divergence level, the number of common operational taxonomic units found between the mothers and children increased as the children aged. Proteobacteria, Bacteroidetes, Firmicutes, Fusobacteria, and Actinobacteria accounted for more than 80% phyla of each group. A microbial community structure analysis showed that the differences between mothers and children were significant in all groups except for the MEG24 and CEG24 groups. Conclusions: Oral microbiota of children was more like their mothers’ with increasing age, regardless of whether the mothers had dental caries. Mothers with dental caries may have a greater influence on the oral microbiota of children’s than those without dental caries as children age.